Identifikasi Pemanfaatan Alat Permainan Edukatif (APE) dalam Mengembangkan Kognitif Anak Usia 5-6 Tahun di TK Se-Kecamatan Ampenan Tahun 2022 - Marhendra Haryanto Putra; Gunawan Gunawan; I Nyoman Suarta; Baik Nilawati Astini (Indonesian Publication Center, 2022)
It is important to use Educational Game Tools (APE) to gain an understanding of education in children's learning processes. APE is specifically designed to develop aspects of child development, one of which is cognitive. This study aims to find out what APE is used, dominantly used and effectively used in developing the cognitive development of children aged 5-6 years in Kindergartens throughout the Ampenan District in 2022. The type of research used is a survey research type. The sampling technique used was the proportionate stratified random sampling technique, with a population of 129 teachers in group B and a sample of 34 teachers in group B. The data collection tools used were questionnaires and interviews. Data analysis in this study uses percentages. The results of the study showed that 17 APEs were used to develop the cognitive abilities of children aged 5-6 years, then 8 APEs were dominantly used, namely Geometry Blocks, Picture/Shape Cards, Number Blocks, Lego, Animal Puzzles, Ice Cream Sticks, Miniature Fruits/Vegetables and Maze Boards, then APE that is effectively used by all 17 APEs that teachers believe is effective in developing children's cognitive development. There are so many APE available in schools, of course the use of them is influenced by the teacher, it is hoped that the teacher will be able to provide and make the most of APE so that later the cognitive development of children can develop optimally.